The Illusion of populate. Territories, narratives and maps of the Orinoco and Guayana in the second half of the eighteenth century, the Threshold of a human geography of the future (2019)
Under the contemporary space of the American geographies are other spaces that make up a large hypotext whose complexity is integrated by the tradition of geographical discourses while accounting for the changing forms of territorial perception. The geographical history of these spaces was organized and promoted by the illusion of populate and the discourse of progress. This research work reflects on this binomial and interpellates the historicity and geograficity of the territories of the Orinoco basin and Guiana in the 18th century, of the processes and phenomena that articulated it and made it visible. In this sense, geographical narratives, maps and dictionaries constituted repertoires that organized the territorial geographic imagination of the Orinoco and Guayana in the eighteenth century, its review and its synthetic criticism is the subject of this work.